Servants and Masters in 18th-Century France : The Uses of Loyalty - Maza, Sarah C., 1953- (Book collections on Project MUSE., 2014)
Here is the first major study of domestic service in France from the late seventeenth century to the early nineteenth century, describing its transformation from a male-oriented occupation, aristocratic in style and often geared to public display, to one that was female, middle-class, and centered on the household. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the orig.